MODEL MANAJEMEN BIMBINGAN DAN KONSELING KEDAMAIAN UNTUK MEMBANGUN IKLIM SEKOLAH DAMAI - Eva Imania Eliasa, - (2022)
Learning requires a supportive atmosphere from various factors. The atmosphere demand to be systemically developed. Guidance and counseling in education have a prominent role to establish the learning atmosphere. Therefore, peace guidance and counseling management are essential to implement for schools. The study aims to develop a peace guidance and counseling management model to enhance the peaceful school climate. The study was conducted through the three stages that were the preliminary stage, product development, and model implementation. A combination of quantitative and qualitative approaches with the concurrent triangulation design model was employed. Participants were selected with a multistage cluster random sampling technique from a total of 753 high school students in Yogyakarta city. The samples were 32 students in grade ten of the Science Class at the Fourth Senior High School of Yogyakarta based on convenience sampling. In the first stage, the data were analyzed with the Rasch Model and NVIVO, while in the second stage, the data was examined using quantitative and qualitative descriptive approaches. Further analysis was the Anova test to examine the efficacy model that was supported by the qualitative analysis. The results revealed that the students' tendency of peace is in the category of very peaceful, while the teachers are in the peaceful category. The peace guidance and counseling management model is an integration of the students' tendencies, the teacher's capacity, and the perspective of the peaceful concept in guidance and counseling. The implementation of the model began with developing teacher capacity. The results showed that the model had not been able to develop all indicators of peace schools, although, in practice, there was an increase in the students' positive behavior. The model is considered acceptable; however, it requires some improvement before being disseminated to others.